Home language and other socio-cultural factors as correlates of yoruba language achievement of jss3 students of oyo state private secondary schools, Nigeria (2024)
The purpose of this study was to examine Home Language and other socio-cultural variables as correlates of JSS 3 students' Yoruba Language achievement in Oyo State private secondary schools, the study adopted a correlation research design. The target population consisted of all junior secondary III students in Oyo state private schools. A sample size of 1287 respondents was drawn using simple random sampling technique. A fifty items Yoruba Language achievement test and students' questionnaire were the instruments used for the study. The study was guided by four research questions. Mean, Standard deviation and multiple regressions were used to answer the research questions. The findings shows that the overall model of the predictor variables ( age, gender, socio economic status peer group) interaction is not effective in predicting student achievement in Yoruba Language . F(2405=3.149, P<0.05), this implies that the combination of the predictors variables is statistically significant at P<0.05 which indicates that the obtained regression resulting from a set of four predictors age,gender, socio economic status and peer group interaction allows reliable prediction of students achievement in Yoruba Language Home Language and the socio-cultural variables of age, gender, social-class and peer group interact together to correlate with Yoruba Language Achievement of JSS III students in Oyo state private schools. Both the child's home language and English language should be taught at the very basic level of education with the structure and intricacies of both exposed sequentially, from simple to complex. Children should be alloyed to belong to legitimate groups to encourage ease in language use, teachers should vary in their teaching methods to accommodate learners of all age and abilities, both males and females should be encouraged in their educational endeavours, teachers should identify specific challenges of learners from poor homes as well as those from rich homes, continuous training and re-training of teachers of Yoruba Language should be considered a priority